Exposure to family planning messages on social media and its association with maternal healthcare services in Mauritania - Bishwajit Ghose; Nicholas Kofi Adjei; Sanni Yaya (BMC, 2024)
Abstract Background Mauritania, a lower-middle-income country in Northwest Africa, has one of the highest maternal and infant mortality rates worldwide and struggles to ensure optimal use of maternal healthcare services. Raising health awareness through family planning messages can promote maternal healthcare use, potentially reducing preventable maternal and child mortalities. The objective of the study was to assess the potential impact of exposure to family planning messages through social media on the utilization of maternal healthcare services among Mauritanian women. Methods Data from the 2019-20 Mauritania Demographic and Health Survey (MDHS) on 7,640 women were analyzed. Multiple logistic regression models were applied to examine the associations between exposure to family planning messages through social media and maternal healthcare services, specifically the timing and adequacy of ANC visits, and facility-based childbirth. Adjusted odds ratios with 95% confidence intervals (CI) were estimated. Results The percentage of timely initiation and adequate use of ANC among the participants were 65.6% and 45.1%, respectively. Approximately 75.0% of the women reported giving birth to their last child at a healthcare facility. Exposure to family planning messages on social media was significantly associated with increased odds of receiving adequate antenatal care visits (OR = 1.38, 95% CI = 1.12,1.71) and giving birth in a health facility (OR = 1.83, 95% CI = 1.09,3.08), Other factors such as age, health insurance, wealth, and desired timing of the last child were also found to be important predictors of maternal healthcare. Conclusion The findings suggest that exposure to family planning messages on social media is strongly associated with adequate antenatal care and health facility-based childbirth, but not with early timing of antenatal care. Comprehensive maternal healthcare policies should consider the role of social media in promoting family planning messages.